Analysis of Albert Bandura's Social Learning Theory in Recognizing Students' Interests and Talents - Sri Bintang Abadi; Khoirunnisa Alfadhillah; Putri Salisatu; Tarsono (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to examine how Albert Bandura's social learning theory can be applied in the context of Islamic Religious Education (PAI) to help teachers identify and develop students' interests and talents. This study uses a qualitative approach with a library research method. The data used in this study consists of primary and secondary sources. Primary sources include Albert Bandura's book "Social Learning Theory," while secondary data are obtained from journal articles and relevant documents. Data collection techniques are carried out through identification, selection, and content analysis, with steps including data reduction, data presentation, and conclusion drawing. The research findings suggest that Albert Bandura's social learning theory provides an effective theoretical and practical framework to assist teachers in identifying and developing students' interests and talents, particularly in Islamic Religious Education (PAI). Using observational learning and modeling approaches, this theory provides a relevant foundation for teachers to understand students' potential through analyzing students' attention, retention, motor reproduction, and motivation in various learning activities. The modeling concept, which emphasizes the importance of teacher role models, is highly in line with the principle of uswatun hasanah in Islamic education, where teachers not only act as transmitters of material but also as models of Islamic behavior.